Do Demand or Supply Factors Drive Bank Credit, in Good and Crisis Times? - Gabriel Jiménez; Steven Ongena; José-Luis Peydró; Jesuś Saurina (Universitat Pompeu Fabra (upf), Department of Economics and Business, 2017)
We analyze the impact of balance-sheet strength on credit availability. Bank balance sheets are weak in crisis times, but so are those of firms, and credit demand is then also weak. For identification, we exploit an administrative dataset of loan applications matched with bank and firm variables covering Spain from 2002 to 2010. Bank balance-sheet strength determines the granting of loan applications only in crisis times, while firm balance-sheet strength – notably leverage – determines strongly this granting in both good and crisis times. Our findings underscore the importance of the strength of corporate balance sheets over credit supply for credit availability.
Keywords: E44; G01; G28; G32; 330; firm balance-sheet channel; credit demand; bank lending channel; credit supply; business cycle; credit crunch; leverage